2021
DOI: 10.1021/acsami.1c03083
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Photochromic Triphenylamine into a Zirconium–Organic Framework for Highly Effective Photocatalytic Aerobic Oxidation of Sulfides

Abstract: A zirconium-based metal–organic framework (MOF) was successfully constructed via solvothermal assembly of a triphenylamine-based tricarboxylate ligand and Zr­(IV) salt, the structure simulation of which revealed that it possesses a two-dimensional layered framework with a relatively rare dodecnuclear Zr12 cluster as the inorganic building unit. The inherent photo-responsive property derived from the incorporated photochromic triphenylamine groups combined with its high stability makes the constructed MOF an ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 53 publications
3
55
0
Order By: Relevance
“…In general, homogeneous catalysts show high catalytic activity under mild conditions, but separation from the products is difficult. , Therefore, the heterogeneous catalysts have attracted considerable attention for CO 2 fixation. Traditional heterogeneous catalysts including metal oxides, ion-exchange resins, polymers, gold nanoparticles, etc., can fulfill the catalyst separation problem but are often restricted by their harsh reaction conditions and high cost. , In recent years, MOF materials have attracted much attention for their high specific surface area and micropores, ordered porous structures, and high adsorption capacity, which render them a variety of catalytic properties and applications in many organic reactions, such as the cycloaddition reaction of CO 2 with epoxides and the Knoevenagel condensation reaction. However, it is still a challenge to construct functional porous MOFs with enough size to allow guest molecules to enter and exit freely, which is subject to the deployment of ingredients and the precise regulation of the growth environment.…”
Section: Introductionmentioning
confidence: 99%
“…In general, homogeneous catalysts show high catalytic activity under mild conditions, but separation from the products is difficult. , Therefore, the heterogeneous catalysts have attracted considerable attention for CO 2 fixation. Traditional heterogeneous catalysts including metal oxides, ion-exchange resins, polymers, gold nanoparticles, etc., can fulfill the catalyst separation problem but are often restricted by their harsh reaction conditions and high cost. , In recent years, MOF materials have attracted much attention for their high specific surface area and micropores, ordered porous structures, and high adsorption capacity, which render them a variety of catalytic properties and applications in many organic reactions, such as the cycloaddition reaction of CO 2 with epoxides and the Knoevenagel condensation reaction. However, it is still a challenge to construct functional porous MOFs with enough size to allow guest molecules to enter and exit freely, which is subject to the deployment of ingredients and the precise regulation of the growth environment.…”
Section: Introductionmentioning
confidence: 99%
“…The only relevant Zr-MOF built from the same organic linker is Zr 12 -NBC, which was obtained as fine powder and structurally characterized by powder X-ray diffraction (PXRD). 48 SCXRD analysis revealed that Th-SINAP-200 crystallizes in the triclinic space group P 1̄. Owing to the cationic feature of Th-SINAP-200 (discussed later), all eight O atoms on the Th 6 core were assigned as μ 3 -OH groups, affording a Th 6 (μ 3 -OH) 8 hexameric SBU ( Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Outstandingly, the photocatalytic efficiency of CCNU-16 is obviously superior to those of the reported MOFs-based photocatalysts UNLPF-10, NNU-45, and Zr 12 -NBC (Table S8 †). 28,30,62 In particular, it is higher than that of inorganic semiconductor photocatalysts, such as surface-modied TiO 2 , 63a-c and common transition-metal oxides semiconductor ARS-Nb 2 O 5 (ref. 63d) (Table S8, † entries [15][16][17][18][19].…”
Section: Photocatalytic Oxidation Of Suldesmentioning
confidence: 99%
“…Over the past several years, a few MOFs have been developed as potential heterogeneous photocatalysts for photochemical synthesis. [28][29][30][31][32] Despite the great progress, MOFs capable of photocatalytic organic transformations are in the infancy stage, and the performance still has a large space to achieve. It is therefore important to exploit and screen more efficient and versatile MOF photocatalysts for the selective aerobic oxidation of amines or suldes, especially under environmentally benign conditions.…”
Section: Introductionmentioning
confidence: 99%